Prevalence and associated factors of postpartum depression among postpartum mothers in central region, Eritrea: a health facility based survey - Nahom Kiros Gebregziabher; Tesfit Brhane Netsereab; Yerusalem Gebremeskel Fessaha; Feven Andebrhan Alaza; Nardos Kidane Ghebrehiwet; Aman Hadish Sium (BMC, 2020)
Abstract Background Postpartum depression (PPD) is a mood disorder that occurs within the first 12 months after delivery. It affects 20 to 40% of women living in the low-income countries. In resource limited countries discovering the predictors of PPD is important as it allows close follow-up and targeted screening of at risk mothers. The objective of this study was to assess the magnitude and predictors of PPD among recently delivered mothers in Central Region of Eritrea. Methods This study used analytical cross-sectional study design to evaluate the magnitude of and factors associated with postpartum depression among 380 randomly selected mothers. The study was conducted in four primary health care facilities of Zoba Maekel (Central Region), Eritrea. A structured closed-ended questionnaire was used to capture the socio-demographic and maternity related information of the study participants. The standard Diagnostic and Statistical Manual of Mental Disorders Fifth Edition was used to assess depression. The dependent variable for this study was status of the mother with regard to PPD. The socio-demographic and maternity related variables of the mothers, presumed to influence the likelihood of developing postpartum depression, were the independent variables. Results In this study the prevalence of PPD was found to be 7.4%. Mother's who are housewives were less likely to develop PPD (AOR = 0.24, 95% CI: 0.06-0.97; p = 0.046), whereas, mothers with perceived low economic status (AOR = 13.33, 95% CI: 2.66-66.78; p = 0.002), lack of partner support (AOR = 5.8, 95% CI: 1.33-25.29; p = 0.019), unplanned pregnancy (AOR = 3.39, 95% CI: 1.24-9.28; p = 0.017), maternal illness after delivery (AOR = 7.42, 95% CI: 1.44-34.2; p = 0.016), and reside in Southwest-Asmara (AOR = 6.35, 95% CI: 1.73-23.23; p = 0.05) had statistically significant higher odds of postpartum depression. Conclusions In the current study setting, factors that associated with PPD are grouped in to two domains; the woman's potential to bear the forthcoming responsibility and the social support they get after delivery. The findings of this study imply the need to introduce an active screening program for PPD the health facilities as part of the postpartum care.